A latent structural analysis of health behaviors among people living with spinal cord injury. Issue 3 (March 2018) - Li, Chao; DiPiro, Nicole; Krause, James
Abstract Study design Cross-sectional study. Objectives To develop a latent structural model of health behaviors among people with spinal cord injury (SCI) that accounts for measurement of underlying factors and their association with demographic and injury-related variables. Setting The data were collected at a large specialty hospital and analyzed at a medical university in the Southeastern United States. Methods A total of 1871 participants with traumatic SCI of at least 1-year duration were included. Exploratory factor analysis (EFA) was used to identify the latent health behavior structures. Several key exogenous variables were also linked with the latent health behavior factors. Results Five latent health behavior factors were identified by the EFA with excellent model fit (root mean square error of approximation = 0.043). These latent factors included (1) medication non-compliance, (2) prescription medication and substance use, (3) smoking, (4) alcohol consumption, and (5) healthy lifestyle activities and participation. Sex, race/ethnicity, age, years since injury, and injury severity were all significantly associated with at least one latent health behavior factor. For instance, men scored higher in smoking and alcohol consumption, whereas women scored higher in prescription medication and substance use. Non-whites scored higher on the medication non-compliance dimension and lower on the healthy lifestyle activities and participation dimension. Conclusions Utilization of latent health behavior factors provides more stable and comprehensive composite scores than does a single observed health behavior indicator. There are important differences in behaviors based on individual characteristics.